Managing Creativity: A Critical Examination, Synthesis, and New Frontiers. Issue 4 (20th July 2016) - Slavich, Barbara; Svejenova, Silviya
Abstract : This article aims at providing definitional clarity on creativity and a systematic understanding of its management in organizations. By drawing on the results of a content analysis of creativity definitions in 440 scholarly publications in the field of management between 1990 and 2014, this study clarifies how scholars in the management domain have defined the concept and identifies core categories shared by these definitions. It also brings together these conceptual categories into an integrative multilevel framework of relevance for managing creativity in organizations. The framework outlines a view of managing creativity, which involves managing interconnected processes as well as dualities, such as processes‐outcomes, individuals‐collectives, and permanent‐temporary creativity units. Finally, it paves the way to new research frontiers for the domain.